Differentiation Strategies for the export of palta Hass (Persea Americana Mill) from the company Agrícola Agrícola Yotita S.A. To Germany - 2016 - Suárez Mendoza, Gianella Estefany (2017)
The present research had as main objective: To propose differentiation strategies to improve the export of avocado Hass from the company Agrícola Agrícola Yotita destined to Germany 2016 ". To do this, it focused on the differentiation strategies of Keller & Kotler, which determine that a company can be perceived by customers as unique. To obtain the information it has taken into account three populations:, which are the following : The collaborators of the company Negociación Agrícola Yotita SA (organization under study); Hass avocado exporters, such as Tropical Farm S.A.C, Fruit Consortium Lambayeque S.A.C and Agrícola Cerro Prieto S.A; And finally specialists in foreign trade issues: Lic. Paola Corvacho Valderrama and Dr. Carlos Querevalú Morante, who were given the Interview Guide in depth. According to the results, it is concluded that the differentiation strategies constitute an effective way to increase exports, in this case the Hass avocado from the company Negociación Agrícola Yotita SA, in the aspect of the product through the most up-to-date international certification as The GlobalG.AP 5.0, with respect to the personnel, differentiation is achieved through courses or trainings mainly in the management of Hass avocado cultivation; And as a third aspect through the image, that is to say that the image of the company is consolidated in the mind of the consumer through the international fair Fruit Logística in Germany; Allowing the optimization of Hass avocado exports to the German market.